2016
DOI: 10.4251/wjgo.v8.i5.439
|View full text |Cite
|
Sign up to set email alerts
|

Current adjuvant treatment modalities for gastric cancer: From history to the future

Abstract: The discrepancy between the surgical technique and the type of adjuvant chemotherapy used in clinical trials and patient outcomes in terms of overall survival rates has led to the generation of different adjuvant treatment protocols in distinct parts of the world. The adjuvant treatment recommendation is generally chemoradiotherapy in the United States, perioperative chemotherapy in the United Kingdom and parts of Europe, and chemotherapy in Asia. These options mainly rely on the United States Intergroup-0116,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…Although stomach cancer has a poor prognosis, the increases in overall survival for all stages between the 2 periods are positive, especially because there was an increase in the proportion of the types with the worst prognosis—cardia and diffuse—in the total pool of stomach cancers. The improvement in survival for each stage could be because of better therapy regimens or more access to appropriate treatment …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although stomach cancer has a poor prognosis, the increases in overall survival for all stages between the 2 periods are positive, especially because there was an increase in the proportion of the types with the worst prognosis—cardia and diffuse—in the total pool of stomach cancers. The improvement in survival for each stage could be because of better therapy regimens or more access to appropriate treatment …”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is by endoscopy and biopsy; computed tomography scans of the chest, abdomen, and pelvis are required to determine stage at diagnosis . Adjuvant chemotherapy and chemoradiotherapy after resection of stomach cancer offer survival benefits, but the discrepancies between the surgical technique and type of adjuvant chemotherapy used in clinical trials and survival probabilities have resulted in different adjuvant treatment protocols . The major challenge for clinicians is treatment sequence .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the majority of patients (54%) in the INT0166 trial underwent a D0 lymphadenectomy (7). Additionally, improvement in radiation therapy delivery modalities (19) and changes in chemotherapy regimens (20) during recent years might have contributed to improved outcomes observed for CRT. It has also been argued that the benefits of CRT observed in INT0166 trial resulted from adjuvant therapy merely compensating for inadequate surgery (21).…”
Section: Discussionmentioning
confidence: 99%
“…Curative resection is the treatment of choice for patients with gastric cancer; however, according to several recent large-scale studies, only 30%–50% of patients with gastric cancer remain disease-free after undergoing radical resections [ 2 3 ]. A large proportion of patients are diagnosed with loco-regionally advanced disease, which results in high loco-regional and distant recurrence rates, with poor survival [ 4 5 ]. For patients with potentially curable gastric cancer, randomized trials have indicated that a number of approaches, including postoperative adjuvant chemotherapy, can provide significant survival benefits over surgery alone [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%